2004
DOI: 10.1136/jnnp.2003.018135
|View full text |Cite
|
Sign up to set email alerts
|

Hyperekplexia and stiff-man syndrome: abnormal brainstem reflexes suggest a physiological relationship

Abstract: Background and objectives: Hyperekplexia and the stiff-man syndrome (SMS) are both conditions with exaggerated startle suggesting abnormal brainstem function. Investigation of brainstem reflexes may provide insight into disturbed reflex excitation and inhibition underlying these movement disorders. Patients and methods: Using four-channel EMG, we examined four trigeminal brainstem reflexes (monosynaptic masseter, masseter inhibitory, glabella, and orbicularis oculi blink reflexes) and their spread into pericra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Little or no response to visual and vestibular stimuli was recorded 72. Further evidence of altered supraspinal-inhibitory mechanisms has been reported with brainstem reflexes frequently showing increased excitation with hyper-synchronisation of multiple muscles, decreased inhibition and short-response latencies with a pattern similar to that observed in patients with hyperekplexia 73. An enhanced recovery cycle in the late (R2) component of the blink reflex is another feature of brainstem hyperexcitability in patients with SPS 74…”
Section: Neurophysiological Studies and Functional Imagingmentioning
confidence: 86%
“…Little or no response to visual and vestibular stimuli was recorded 72. Further evidence of altered supraspinal-inhibitory mechanisms has been reported with brainstem reflexes frequently showing increased excitation with hyper-synchronisation of multiple muscles, decreased inhibition and short-response latencies with a pattern similar to that observed in patients with hyperekplexia 73. An enhanced recovery cycle in the late (R2) component of the blink reflex is another feature of brainstem hyperexcitability in patients with SPS 74…”
Section: Neurophysiological Studies and Functional Imagingmentioning
confidence: 86%
“…18 A study of trigeminal brainstem reflexes in patients with SMS suggested primary dysfunction of the inhibitory interneurons at the brainstem level. 19 In contemporary practice, neurologists generally reserve GAD65 antibody testing for patients who present with SMS, idiopathic cerebellar ataxia, or juvenile epilepsy. The fact that GAD65 antibody testing was not requested by the clinician for any patient in our study supports this practice.…”
Section: Discussionmentioning
confidence: 99%
“…The term "stiffman" is a misnomer, since women have long been recognized to be equally affected (Editorial 1967). Abnormally increased brain stem excitability and reflexes with exaggerated startle have been reported to occur in this condition (Molloy et al 2002;Khasani et al 2004). Abnormally increased brain stem excitability and reflexes with exaggerated startle have been reported to occur in this condition (Molloy et al 2002;Khasani et al 2004).…”
Section: Stiff-man (Stiff-person) Syndrome (Moersch-woltman Syndrome)mentioning
confidence: 91%
“…Stiff-person syndrome is of spinal or brainstem origin (Molloy et al 2002;Khasani et al 2004) and shows evidence of being an autoimmune disease (McEvoy 1991;Layzer 1994;Vogels et al 2003). The standard treatment for this condition has been benzodiazepines (McEvoy 1991).…”
Section: Stiff-man (Stiff-person) Syndrome (Moersch-woltman Syndrome)mentioning
confidence: 99%